The Influence of Gender Inequality in the Development of Job Insecurity: Differences Between Women and Men - Sara Menéndez-Espina; Jose Antonio Llosa; Esteban Agulló-Tomás; Julio Rodríguez-Suárez; Rosana Sáiz-Villar; Héctor Félix Lasheras-Díez; Hans De Witte; Hans De Witte; Joan Boada-Grau (Frontiers Media S.A., 2020)
Job insecurity is an indicator of precarious work that refers to the fear of losing one's job. It is a relevant source of stress, with negative consequences on people's mental health. The main objective and contribution of this study is to identify how gender inequality and job insecurity are related, responding to the lack of consensus found in scientific literature in this field of study. To do so, a predictive study of job insecurity, broken down by gender, is developed, considering sociodemographic and labor variables as antecedents. The sample included 1,005 employees (420 men and 585 women) aged between 18 and 65, and a linear regression was conducted for each group. Results show that women perceive greater insecurity under precarious working conditions (temporary work, informal work, salary cuts, tenure), whereas in the case of men variables related to their professional careers (job category, education) and household incomes were relevant predictors. It is concluded that job insecurity affects both gender groups, but the conditions in which this perception grows are significantly impacted by gender inequality. These findings will allow for holistic and effective actions to decrease the effects of precarious work.